2014
DOI: 10.1038/ncomms6181
|View full text |Cite
|
Sign up to set email alerts
|

A viral peptide that targets mitochondria protects against neuronal degeneration in models of Parkinson’s disease

Abstract: Mitochondrial dysfunction is a common feature of many neurodegenerative disorders, notably Parkinson's disease. Consequently, agents that protect mitochondria have strong therapeutic potential. Here, we sought to divert the natural strategy used by Borna disease virus (BDV) to replicate in neurons without causing cell death. We show that the BDV X protein has strong axoprotective properties, thereby protecting neurons from degeneration both in tissue culture and in an animal model of Parkinson's disease, even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 60 publications
3
60
0
Order By: Relevance
“…In previous studies we showed that axo-protective molecules impaired both mitochondrial fission and axonal degeneration processes1340. Here, in order to assess whether fission could be a cause or a consequence of ongoing axonal degeneration, we investigated the direct role of mitochondrial dynamics on spontaneous axonal degeneration.…”
Section: Resultsmentioning
confidence: 97%
“…In previous studies we showed that axo-protective molecules impaired both mitochondrial fission and axonal degeneration processes1340. Here, in order to assess whether fission could be a cause or a consequence of ongoing axonal degeneration, we investigated the direct role of mitochondrial dynamics on spontaneous axonal degeneration.…”
Section: Resultsmentioning
confidence: 97%
“…In low-intensity stimulation (LI-rMS) studies, solenoids (Di Loreto et al, 2009; Varro et al, 2009) or coils made “in house” have been applied to one-off experiments on cultured neurons/slices (Ahmed and Wieraszko, 2009; Rotem et al, 2014) or isolated nerves (Maccabee et al, 1993; Basham et al, 2009; RamRakhyani et al, 2013; Ahmed and Wieraszko, 2015) that do not permit on-going stimulation sessions to model treatment-based protocols. Moreover, given that NIBS acts on complex neural circuits, stimulation parameters should ideally be assessed in culture models which retain some neural circuitry: e.g., organotypic hippocampal (Hausmann et al, 2001; Hogan and Wieraszko, 2004; Vlachos et al, 2012; Lenz et al, 2016) and cortico-striatal slices, hindbrain explants (Chedotal et al, 1997; Letellier et al, 2009) or microfluidic circuit cultures (Szelechowski et al, 2014). However, these diverse culture systems have unique dimensions and culture conditions, highlighting the need to establish a reliable and flexible LFMS/LI-rMS system that can be tailored to deliver a defined magnetic field that induces an electric field of predicted intensity and direction at a particular location within each culture.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanistic bases of these effects are not fully understood, mitochondria could be a potential target. Szelechowski found C-terminal end of the X protein was able to protect against neurodegeneration by buffering mitochondrial damage and inducing enhanced mitochondrial filamentation (Szelechowski et al, 2014). Kuan found human cytomegaloviral β2.7 transcript derived noncoding p137 RNA can prevent and rescue dopaminergic cell death by protecting mitochondrial Complex I activity (Kuan et al, 2012).…”
Section: Discussionmentioning
confidence: 98%